Coupling of discrete element model (DEM) with computational fluid mechanics (CFD): A validation study - Iqbal, Naveed; Rauh, Cornelia (Applied Mathematics and Computation, 2016)
A numerical model is developed in the framework of OpenFOAM; an open source computational fluid dynamics (CFD) simulation code to simulate particle laden dense flows. The model uses discrete element method (DEM) for the discrete/particle phase and computational fluid dynamics approach (CFD) for the fluid/continuum phase. In current study, validation of the model is done in two steps. In first step the drag model is validated by comparing the results of settling velocity of spherical particle. In second step, spout fluidization test cases with different operating conditions are simulated and results of numerical simulation of spout-fluidized bed are compared against experimental and simulation results reported in literature. The isosurface plots of solid volume fraction show a good qualitative prediction of different flow regimes. The particle velocity profiles in the vertical direction for different test cases corresponding to different flow regimes are plotted and compared with the literature data. The predictions of the model are in good agreement with the experimental and numerical results reported in the literature.
UnivIS-Import:2016-06-01:Pub.2016.tech.ITC.stmmec.coupli
Keywords: CFD-DEM; Eulerian-Lagrangian; Fluidization; Jet flows; Spout fluidization